1996
DOI: 10.1073/pnas.93.1.326
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional transactivator of simian foamy virus 1 binds to a DNA target element in the viral internal promoter.

Abstract: The transcriptional transactivator (Tas) of simian foamy virus type 1 strongly augments gene expression directed by both the promoter in the viral long terminal repeat and the newly discovered internal promoter located within the env gene. A region of 121 bp, located immediately 5' to the TATA box in the internal promoter, is required for transactivation by Tas. The present study aimed to identify the precise Tas-responsive target(s) in this region and to determine the role of Tas in transcriptional regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 28 publications
5
40
0
Order By: Relevance
“…It is well known that Bel1 activates both HFV promoters by direct binding to short defined but promiscuous DNA target sequences of the FV promoters (9,10,33) and that for full transactivation levels, interactions of Bel1 with unknown cellular proteins seem to be required (10). Since the potent Bel1 transactivator has the capacity to bind different DNA target sequences, it is likely that Bel1-mediated activation of cellular genes proceeds by a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Bel1 activates both HFV promoters by direct binding to short defined but promiscuous DNA target sequences of the FV promoters (9,10,33) and that for full transactivation levels, interactions of Bel1 with unknown cellular proteins seem to be required (10). Since the potent Bel1 transactivator has the capacity to bind different DNA target sequences, it is likely that Bel1-mediated activation of cellular genes proceeds by a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into the mechanism of repression, we focused on the core IP.BRE region from Ϫ166 to Ϫ116 that allowed us to define the roles of NFI and Bel1 proteins in DNA binding by carrying out EMSAs, supershifts, and competition EMSAs. Several groups have reported that Bel1 binds its target sequence directly (10,16,23). The minimal IP.BRE of 27 bp seems to be the one with a high DNA binding affinity compared with the corresponding LTR BRE (10).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Bel1 is initiated at the IP until threshold levels of the Bel1 transactivator are reached which subsequently turn on the 5Ј-LTR promoter to direct synthesis of virus structural proteins (13)(14)(15). The transactivator Tas of simian foamy virus type 1 binds to corresponding proximal and distal DNA target sites directly that are not homologous to the Bel1 response element (BRE) of the IP (16). Bell 1 was shown to be a nuclear protein (17,18) that contains at least two domains, a centrally located DNA binding region and a C-terminal activation domain (19).…”
mentioning
confidence: 99%
“…FVs transactivators of different genera have been named differently; the simian FVs transactivator, for example, was termed taf. However the First International Foamy Virus Meeting determined that these transactivators, including Taf and Bel1, should be designated Tas (Zou et al, 1996). The activity of the functional IP and P of FVs depends on this transactivator.…”
Section: Tasmentioning
confidence: 99%